2010
DOI: 10.1029/2008jd011609
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term tendencies in the mesosphere/lower thermosphere mean winds and tides as observed by medium‐frequency radar at Tirunelveli (8.7°N, 77.8°E)

Abstract: [1] The present study examines changes in monthly mean winds and tides observed by MF radar at Tirunelveli (8.7°N, 77.8°E) for the years 1993-2007 with respect to long-term variabilities, namely, the stratospheric quasi-biennial oscillation (QBO), the El Niño-Southern Oscillation (ENSO), the solar cycle (SC), and the long-term trends, using regression analysis. Both zonal and meridional winds show negative QBO response in the altitude region 84-94 km and negative ENSO response (∼1 m s −1 per Southern Oscillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 44 publications
5
34
0
Order By: Relevance
“…Moreover, the O abundance is too low and its lifetime is shorter (few seconds) in the upper stratosphere for the collisional excitation of CO 2 molecule, and thus, the SC response is comparatively smaller in the upper stratosphere than in the upper mesosphere (above 80 km). In addition, since the QBO and ENSO are the prominent interannual variabilities in tropical middle atmosphere (e.g., Sridharan et al, ; Lee et al, , and references therein; Li et al, ), the present study also showed their responses to CO 2 cooling in the SMLT region. The positive responses are larger in the upper mesosphere than at lower heights in association with the solar insolation and dynamical effects.…”
Section: Summary and Discussionsupporting
confidence: 67%
“…Moreover, the O abundance is too low and its lifetime is shorter (few seconds) in the upper stratosphere for the collisional excitation of CO 2 molecule, and thus, the SC response is comparatively smaller in the upper stratosphere than in the upper mesosphere (above 80 km). In addition, since the QBO and ENSO are the prominent interannual variabilities in tropical middle atmosphere (e.g., Sridharan et al, ; Lee et al, , and references therein; Li et al, ), the present study also showed their responses to CO 2 cooling in the SMLT region. The positive responses are larger in the upper mesosphere than at lower heights in association with the solar insolation and dynamical effects.…”
Section: Summary and Discussionsupporting
confidence: 67%
“…Rather, it appears that the dynamo electric field slightly decreases when the solar activity is high. It may be unnatural that the neutral wind velocity is slower under higher solar activity condition, but in fact, it is not surprising because some observations [e.g., Liu et al, 2004;Sridharan et al, 2010] showed that the thermospheric tidal wind velocity is smaller during high solar activity period. This effect is likely attributed to the larger ion drag force owing to larger ion density.…”
Section: Resultsmentioning
confidence: 99%
“…The establishment of ground-based radars at both equatorial and polar latitudes enhanced the spatial/temporal coverage originally available from the predominately mid-latitude stations that prevailed before 2000 (e.g. Mitchell et al 2002;Sridharan et al 2010;Nozawa et al 2012;Davis et al 2013). New instruments, notably lidars that provide daytime observations, also came on line (e.g She et al 2002).…”
Section: Atmospheric Tides In the Mltmentioning
confidence: 96%